Elizabethan Music and Musical Criticism - Boyd, Morrison Comgys (Philadelphia University of Pennsylvania, 1962)
The period represented by the reigns of Queen Elizabeth I and King James I of England was noteworthy not only for its literature and art but for its music. This volume offers a summary of the works on music theory published in England during that period, and illuminates Elizabethan attitudes toward music in theory and practice. Some of the works summarized treat elementary subjects such as scales, time signatures, and the correct use of chords; some take up more complex themes, such as advanced counterpoint, canon, and composition. Other sources provide detailed descriptions of common instruments, and discuss their use in composition and in the home. In addition to quoting many Elizabethan commentators on the proper use of music in the schools and in the church, the author cites Puritan attacks on music. He includes information on all the leading cathedral organists, as well as on choirboy actors and their organist teachers, and he devotes a chapter to the use of music in the plays of Shakespeare and others. Although it was the author's original intention to present only criticism written by Elizabethans, he decided to include, as a necessary aid to the reader, a brief description of the music criticized and to add a modern appraisal of it. Consequently, since all the books of compositions published in the years 1558-1625, chiefly madrigal and lute pieces, but also some church music are mentioned, with some comment on both the music and their composers, Dr. Boyd's study will serve as an excellent short history of Elizabethan music.
Keywords: Elizabeth I -- Queen of England -- 1533-1603; 16th Century (1501-1600); 17th Century (1601-1700); Music history; Music theory; Music criticism; Lute; Madrigal; Music history; Church music; United Kingdom